Claves para la definición de un paisaje cultural : arqueología, patrimonio, didáctica y turismo en la cuenca del Guadalquivir - Vaquerizo Gil, D.; Ruiz Osuna, Ana B., 1980-; Vázquez-Navajas, Belén (Archaeopress Archaeology, 2023)
The Guadalquivir River has been a feature of the identities of the communities settled around it throughout history. This volume reflects on contemporary threats to the sustainability of the region's complex cultural landscapes from multiple perspectives, including archaeology, the natural environment, didactics, new technologies and tourism.